Variability in Intravenous Insulin Infusion Management in Italian Intensive Care Units: A National Cross‐Sectional Survey of Reported Nursing Practice - Carmelo Pujia; Giuseppe Neri; Helenia Mastrangelo; Giuseppe Mazza; Eugenio Biamonte; Caterina Mercuri; Vincenzo Bosco; Tiziana Montalcini; Eugenio Garofalo (Nursing in Critical Care, 2026)
ABSTRACT Background Hyperglycaemia is common in critically ill patients and is associated with increased morbidity and mortality. Continuous intravenous insulin infusion is widely used for glycaemic control in intensive care units; however, its implementation is complex and requires frequent monitoring and substantial nursing involvement. Aims To describe reported practices in continuous intravenous insulin infusion management across Italian intensive care units and to explore variability in glycaemic targets, insulin initiation thresholds, glucose measurement methods and monitoring frequency according to healthcare setting. Study Design A national cross‐sectional survey. A structured questionnaire was distributed to intensive care unit nurses and nurse coordinators in Italy between September and November 2025. Data were collected on institutional characteristics, insulin infusion protocols, glycaemic targets, initiation thresholds, glucose measurement methods and monitoring practices. Exploratory comparisons by healthcare setting used cross‐tabulations and exact tests, as appropriate. Results A total of 128 valid responses were analysed. Standardised insulin infusion protocols were reported by 119 respondents (93.0%), but considerable variability was observed in reported practice. The most commonly reported insulin initiation threshold was 180 mg/dL (50.0%). Exploratory comparisons suggested differences across healthcare settings in initiation thresholds, glucose measurement methods and monitoring frequency before glycaemic stabilisation. The median reported monitoring interval before stabilisation was 120 min (interquartile range 60–240), exceeding the recommended hourly frequency during glycaemic instability. Conclusions Despite widespread reported protocol availability, substantial variability remained in reported continuous intravenous insulin infusion management, particularly in initiation thresholds, glucose measurement methods and monitoring before glycaemic stabilisation. Because workload, staffing and protocol adherence were not directly measured, they should be considered possible explanations rather than study findings. Relevance to Clinical Practice The findings support review of local insulin infusion protocols, explicit monitoring intervals during glycaemic instability, staff education, audit and feedback and escalation processes when glucose checks are delayed.